2010
DOI: 10.1002/jcp.22229
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of a role for eukaryotic translation initiation factor 5A (eIF5A) in mouse embryogenesis and cell differentiation

Abstract: Eukaryotic translation initiation factor 5A (eIF5A) has a unique character: the presence of an unusual amino acid, hypusine, which is formed by post-translational modifications. Even before the identification of hypusination in eIF5A, the correlation between hypusine formation and protein synthesis, shifting cell proliferation rates, had already been observed. Embryogenesis is a complex process in which cellular proliferation and differentiation are intense. In spite of the fact that many studies have describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
(56 reference statements)
0
24
0
Order By: Relevance
“…CNOT6L is a subunit of the CCR4 complex [25], which controls gene expression at multiple levels, including shortening of mRNA polyA tails in the cytoplasm, and a repressor of p27, a proliferation inhibitor required for differentiation [26]. Exportin-4 (XPO4) is a nuclear export protein that inhibits EIF5A2 [27], a translation regulator that seems to be important for skeletal muscle cell differentiation [28].…”
Section: Discussionmentioning
confidence: 99%
“…CNOT6L is a subunit of the CCR4 complex [25], which controls gene expression at multiple levels, including shortening of mRNA polyA tails in the cytoplasm, and a repressor of p27, a proliferation inhibitor required for differentiation [26]. Exportin-4 (XPO4) is a nuclear export protein that inhibits EIF5A2 [27], a translation regulator that seems to be important for skeletal muscle cell differentiation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Gabarap is a known atrophy gene (24) and is upregulated in cisplatin-induced atrophy of C2C12 myotubes (9). Eukaryotic initiation factor 5a (Eif5a) undergoes a unique posttranslational modification (hypusination) that correlates with embryonic myogenic differentiation, and inhibition of EIF5A hypusination impairs C2C12 differentiation (33). Clec10a (MGL1) regulates inflammatory processes, and MGL1 Ϫ/Ϫ mice are protected from glucose intolerance and insulin resistance associated with diet-induced obesity due to diminished adipose tissue macrophage response (44).…”
Section: Discussionmentioning
confidence: 99%
“…Tissues at the stage of differentiation have a higher content of eIF-5A [22]. It has also been reported that eIF-5A stimulates the differentiation and proliferation of various cells, such as multipotent adult germline stem cells, embryonic stem cells and corneal epithelial cells [22,28,29]. However, the mechanism of eIF-5A involved in protein synthesis has been a subject of controversy for decades.…”
Section: 7mentioning
confidence: 99%
“…Up to date, there is no study to address the role of eIF-5A1 in muscle function following SCI. While evidence indicates that eIF-5A is involved in mouse embryogenesis and cell differentiation [22], one report shows that eIF-5A is also involved in stem cell differentiation in skeletal muscle [23], suggesting that eIF-5A could correlate with muscle development and muscle reflex arc plasticity.…”
Section: Introductionmentioning
confidence: 99%